2010
DOI: 10.1093/annonc/mdp427
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of changes in ER, PR and HER2 expression in primary breast cancer and paired nodal metastases

Abstract: A significant number of patients show discordant quantitative expression of molecular markers between primary and nodal disease. Appropriately measured, lymph node receptor status could be a more accurate measurement for guiding adjuvant therapy, which requires testing in a clinical trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
114
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(129 citation statements)
references
References 43 publications
10
114
0
5
Order By: Relevance
“…High expression of these receptors is associated with higher incidence of lymph node metastasis in breast cancer patients [116,117]. A significant number of patients show discordant quantitative expression of molecular markers between primary and nodal disease indicating a organotropy [118]. This concept of organ site specificity corroborates the hypothesis, that lymph node metastases do not further spread or if they do only into lymph nodes down stream the metastatic one.…”
Section: Do Lymph Node Metastases Metastasize?supporting
confidence: 66%
“…High expression of these receptors is associated with higher incidence of lymph node metastasis in breast cancer patients [116,117]. A significant number of patients show discordant quantitative expression of molecular markers between primary and nodal disease indicating a organotropy [118]. This concept of organ site specificity corroborates the hypothesis, that lymph node metastases do not further spread or if they do only into lymph nodes down stream the metastatic one.…”
Section: Do Lymph Node Metastases Metastasize?supporting
confidence: 66%
“…Various studies have reported that the receptor status of metastatic breast cancer may differ from that of the primary tumor (1-4). Aitken et al (14) reported that metastatic lymph node receptor status may be a more accurate parameter for guiding adjuvant therapy. Thus, it is necessary to understand the alterations in tumor phenotype for further therapeutic decision making.…”
Section: Discussionmentioning
confidence: 99%
“…Immunofluorescence for ERa was carried out using methods previously described (28). For slide staining, 3-mm TMA slides were deparaffinized and antigen retrieved by pressure cooking in antigen retrieval buffer (sodium citrate, pH 6.0).…”
Section: Immunofluorescencementioning
confidence: 99%
“…A detailed description of the AQUA HistoRx methodology is available elsewhere (28,29). Pan-cytokeratin antibody was used to identify infiltrating tumor cells, DAPI counterstain to identify nuclei, and Cy5-tyramide detection to target for compartmentalized (tissue and subcellular) analysis of tissue sections.…”
Section: Aqua Automated Image Analysismentioning
confidence: 99%